MENGEMBANGKAN KEMAMPUAN ANAK BERCERITA DENGAN METODE PEMBERIAN TUGAS MENGGAMBAR - Ahmad Fachrurrazi; Sitti Kibtiyah (Bajang Institute, 2022)
This research is motivated by the importance of the development of story-telling ability in early childhood. One of stimulation in the development is the story, as the skills to make a variety of images. With the formulation of the problem is